artikel - nur fadhilah nasution; Luthfiatunnisa Luthfiatunnisa (PKM-P, 2022)
ABSTRACT: Indonesia is a country that has a fairly large population. Based on the results of the Population Census conducted in September 2020, the total population of Indonesia is 270.20 million. So that the large number of people makes Indonesia consisting of a diversity of cultures, religions, ethnicities, and languages. This diversity makes a difference in every level of society. Therefore any differences that exist must be faced wisely. The problem of differences, especially religious issues, is often the thing that causes divisions for the unity and integrity of the Unitary Republic of Indonesia. Sampali village has a community that adheres to several different religions in each hamlet. So in the research conducted in Sampali Village, it is hoped that the community can better understand the true meaning of religious moderation and still be able to uphold the values ​​of brotherhood. This study uses a qualitative descriptive method using several data collection techniques, namely observation, interviews, and documentation. After conducting research in Sampali Village, it can be concluded that the people of Sampali Village quite uphold the values ​​of religious moderation, however, there is still a lack of optimal understanding of religious moderation in several hamlets.